(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2018)
The intercession came in the Holy Quran in the sense of begging to the guardians of God, a desire to escape the calamities or gain mercy or reach a need. In view of the fact that the act of supplication itself is considered, on the basis of what is stated in some of the verses and Islamic Hadiths, a kind of supplication, and the supplication itself is a kind of worship of God Almighty, on this, the question that arises is that is faith in intercession is contrary, Propagation dimension, the first monotheistic origin. Based on this, we will shed light, after we addressed the sections of unification and the conflict, to study the problematic relationship between unification and intercession on two sides, starting from the destinations of Wahhabism. In the beginning, we examine, through studying the historical background, the main factor in this encounter. This article then deals with the relationship between du’aa ’and Tawhid in the Qur’aan, as well as the verses that indicate the convergence between Tawheed and Intercession or the abstention of this encounter. The conclusion of this article is that there is no correspondence between unification and intercession, but there is also a kind of homogeneity and overlap between them.